How Hydrologic Connectivity Regulates Water Quality in River Corridors. (9th October 2018) - Harvey, Jud; Gomez‐Velez, Jesus; Schmadel, Noah; Scott, Durelle; Boyer, Elizabeth; Alexander, Richard; Eng, Ken; Golden, Heather; Kettner, Albert; Konrad, Chris; Moore, Richard; Pizzuto, Jim; et al.
Abstract: Downstream flow in rivers is repeatedly delayed by hydrologic exchange with off‐channel storage zones where biogeochemical processing occurs. We present a dimensionless metric that quantifies river connectivity as the balance between downstream flow and the exchange of water with the bed, banks, and floodplains. The degree of connectivity directly influences downstream water quality — too little connectivity limits the amount of river water exchanged and leads to biogeochemically inactive water storage, while too much connectivity limits the contact time with sediments for reactions to proceed. Using a metric of reaction significance based on river connectivity, we provide evidence that intermediate levels of connectivity, rather than the highest or lowest levels, are the most efficient in removing nitrogen from Northeastern United States' rivers. Intermediate connectivity balances the frequency, residence time, and contact volume with reactive sediments, which can maximize the reactive processing of dissolved contaminants and the protection of downstream water quality. Our simulations suggest denitrification dominantly occurs in riverbed hyporheic zones of streams and small rivers, whereas vertical turbulent mixing in contact with sediments dominates in mid‐size to large rivers. The metrics of connectivity and reaction significance presented here can facilitate scientifically based prioritizations of river management strategies to protect the values and functions of river corridors. Abstract : Research Impact Statement : We quantify river connectivity as the balance between downstream flow and the exchange of water with the bed, banks, and floodplains of rivers, and demonstrate the impact on downstream water quality.